Lower Versus Higher Glycemic Criteria for Diagnosis of Gestational Diabetes. Issue 2 (February 2023) - Crowther, Caroline A.; Samuel, Deborah; McCowan, Lesley M. E.; Edlin, Richard; Tran, Thach; McKinlay, Christopher J.; ,
ABSTRACT: Gestational diabetes mellitus (GDM) in pregnancy is a global health problem. Maternal risks associated with this condition include higher rates of induced labor, cesarean delivery, and preeclampsia. Fetal exposure to GDM can increase the risk of large for gestational age (LGA), as well as operative birth, shoulder dystocia, and birth injuries. To reduce these risks, GDM is managed with nutritional therapy, blood glucose monitoring, and pharmacologic treatment. However, the criteria to diagnose GDM in pregnant individuals vary globally. Although the International Association of Diabetes and Pregnancy Study Groups (IADPSG) recommends using a lower glycemic threshold to diagnose maternal hyperglycemia, its adoption has been mixed. The aim of this study was to evaluate whether lower glycemic criteria to diagnosis GDM would improve perinatal and maternal outcomes. This was a randomized trial conducted in 2 health boards in New Zealand between April 2015 and August 2020. Included were women with singleton pregnancies who had a 75-g oral glucose tolerance test (OGTT) at 24 to 32 weeks of gestation. Excluded were those with diabetes mellitus or a history of GDM. The women were randomly assigned to be evaluated for GDM using lower glycemic criteria for diagnosis or higher criteria in a 1:1 ratio. The lower criteria were defined as a fasting plasma glucose level ≥5.1 mmol/L, a 1-hour level ≥10.1 mmol/L, or a 2-hour level ≥8.5 mmol/L. The higher criterion was a fasting plasma glucose level ≥5.5 mmol/L or a 2-hour level ≥9 mmol/L. The primary outcome was LGA. A total of 4050 women and their infants were randomized and included in the analysis—2019 in the lower criteria group and 2013 in the higher criteria group. There were 8.8% LGA infants born in the lower criteria group and 8.9% in the higher criteria group (unadjusted relative risk, 0.99; 95% confidence interval [CI], 0.81–1.21; P = 0.91). Infants in the lower criteria group were more likely to have hypoglycemia compared with those in the higher criteria group (10.7% vs 8.4%; adjusted relative risk [aRR], 1.27; 95% CI, 1.05–1.54). Women in the lower criteria group were more likely to undergo induced labor (33.7% vs 30.2%; aRR, 1.12; 95% CI, 1.02–1.22) or use pharmaceutical treatment for GDM (10.9% vs 4.6%; aRR, 2.40; 95% CI, 1.90–3.03). They also had more diabetes service visits (0.6 ± 1.6 vs 0.2 ± 1.0; aRR, 2.42; 95% CI, 1.80–3.26), as well as visits with diabetes medical specialists post-OGTT (0.3 ± 0.9 vs 0.1 ± 0.6; aRR, 2.39; 95% CI, 1.80–3.18), diabetes nurses (0.4 ± 1.2 vs 0.2 ± 0.8; aRR, 2.41; 95% CI, 1.80–3.21), and dietitians (0.1 ± 0.3 vs <0.1 ± 0.3; aRR, 2.26; 95% CI, 1.73–2.95). Among women in both groups whose OGTT results were between the lower and higher thresholds, 195 received GDM treatment, and 178 did not. Those in the lower criteria group had fewer LGA infants (6.2% vs 18.%; aRR, 0.33; 95% CI, 0.18–0.62) than those in the higher criteria group. They also experienced less gestational weight gain (10 vs 11.9 kg), had a lower incidence of preeclampsia (0.5% vs 5.6%), were more likely to have labor induced (56.9% vs 30.3%), and had a higher prevalence of breastfeeding when discharged from the hospital (99.5% vs 94.9%). In conclusion, pregnant women evaluated for GDM using lower glycemic criteria group were more than 2.5 times as likely as those in the higher criteria group to receive a diagnosis and treatment. However, despite increased identification and treatment of GDM, the lower glycemic criteria did not result in apparent perinatal or maternal benefit in the population being screened, but some potential benefit was identified in the subpopulation of those with the test values just below the higher threshold.